"Another City, Another Sauna": Travel as Saunatarian Praxis. (3rd October 2018) - Tsonis, Jack
Abstract : This article explores sauna as a religious identity, focusing on the role of travel in the formation of that identity. While the topic of individualist religious/spiritual worldviews has been much discussed in recent sociological literature, so far the literature has not extended to sauna. In large part this is due to the lack of an identifiable Saunatarian community, but this article overcomes that problem by way of autoethnography. Specifically, the article uses personal narrative about my own travel motto ("Another City, Another Sauna") to provide a thick description in response to calls for more data from persons who identify as spiritual tourists. The final section of the article pushes into theoretical terrain: firstly by justifying the label "spiritual tourism" as an appropriate description, then by considering how the idiosyncratic, unpatterned nature of this case study can help to expand our understanding of spiritual tourism as both a category and a phenomenon.